2018
DOI: 10.1002/ghg.1786
|View full text |Cite
|
Sign up to set email alerts
|

Transport of perfluorocarbon tracers in the Cranfield Geological Carbon Sequestration Project

Abstract: A field‐scale carbon dioxide (CO2) injection pilot project was conducted by the Southeast Regional Carbon Sequestration Partnership (SECARB) at Cranfield, Mississippi. Two associated campaigns in 2009 and 2010 were carried out to co‐inject perfluorocarbon tracers (PFTs) and sulfur hexafluoride (SF6) with CO2. Tracers in gas samples from two observation wells were analyzed to construct breakthrough curves. In this work, we present the field data and numerical modeling of the flow and transport of CO2, brine, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…where C f [Pa −1 ] is the mixture compressibility and νi [m 3 /mol] is the partial molar volume of each compo-nent in the mixture; both variables are computed from the CPA-EOS. We adopt the higher-order combination of Mixed Hybrid Finite Element and Discontinuous Galerkin methods that were presented in earlier works [25,[43][44][45][46][47][48][49][50][51] for high-resolution simulations of flow and transport in porous media; more details on the numerical methods and solvers are provided in [52].…”
Section: Formulationmentioning
confidence: 99%
“…where C f [Pa −1 ] is the mixture compressibility and νi [m 3 /mol] is the partial molar volume of each compo-nent in the mixture; both variables are computed from the CPA-EOS. We adopt the higher-order combination of Mixed Hybrid Finite Element and Discontinuous Galerkin methods that were presented in earlier works [25,[43][44][45][46][47][48][49][50][51] for high-resolution simulations of flow and transport in porous media; more details on the numerical methods and solvers are provided in [52].…”
Section: Formulationmentioning
confidence: 99%
“…The captured CO 2 is used to inject into the Cranfield oil field, in southwest Mississippi, USA, for EOR. In addition, the Cranfield oil field is characterized by a complex pressure with a heterogeneous fluvial sandstone channel and an effective aquifer drive, which is difficult to anticipate with regard to the presence of gas in the formation. , Because of this complexity, the monitoring plan was conducted, especially 4D seismic, and the result revealed that there was a mixed success in the formation. ,, Furthermore, they applied a probabilistic technique to the location to develop monitoring tools and sampling frequencies inside and above of the reservoir formation for geophysical and geochemical monitoring assurance …”
Section: Carbon Dioxide Storage In Major Fieldsmentioning
confidence: 99%
“…1,2 There are extensive body of published works about the experimental and numerical aspects of this process. [3][4][5][6][7][8][9] However, high costs of CO 2 sequestration projects are a barrier in this topic. Based on this fact that large amount of costs is invested to purify CO 2 from the flue gas stream of the emission sources, some researchers introduced impure CO 2 sequestration as a way to tackle the economic issues.…”
Section: Introductionmentioning
confidence: 99%